THE CONCEPT OF EDUCATION ACCORDING TO IBN KHALDUN - Widyastuti, Wanti; Lubis, M. Fauzi; Sabri, Rijal (Universitas Dharmawangsa, 2023)
The purpose of this study is to find out: (1) Ibn Khaldun's view of education and to know how the classification of knowledge according to Ibn Khaldun. (2) The curriculum according to Ibn Khaldun. (3) Ibn Khaldun's view of educators and knowing the nature of educators. (4) Ibn Khaldun's view of students and knowing how the learning process is.The method used is descriptive method. Descriptive method is a method used to examine the status of a human group, an object, a set of conditions, a system of thought or a class of events in the present. Thus, this research will examine a system of thought of figures who contribute to the world of education at this time.The results of this study are: (1) The concept of education according to Ibn Khaldun is not only about learning and teaching, but education is a process in which humans consciously capture, absorb and appreciate events that have occurred throughout the ages and learn Arabic as an effort to understand Al-Qur'an. -The Qur'an and the classification of knowledge according to Ibn Khaldun consist of 2, namely Naqliyyah Science and Aqliyyah Science. (2) The curriculum according to Ibn Khaldun consists of 2, Naqliyyah Science sourced from the Qur'an and As-Sunnah and Aqliyyah Science sourced from the human mind. (3) An educator according to Ibn Khaldun is someone who educates, protects, teaches, directs and guides students towards change for the better. (4) Students according to Ibn Khaldun are people who receive knowledge or parties who need guidance and direction from educators in accordance with their physical and spiritual development.